MERCURY DISTRIBUTION IN TRAP ROCKS FROM THE SOUTHERN SIBERIAN PLATFORM - Feoktistov G.D. (My University, 2001)
The study of mercury distribution in trap rocks from the southern Siberian Platform based on 260 determinations has shown that background Hg contents in trap sills pertaining to different intrusive phases are approximately equal (4.8 × 10-6 and 4.5 × 10-6 wt %) and close to the clarke value in the Earth's crust. Intrachamber fractionation does not affect mercury distribution. The hydrothermal alteration of trap rocks in iron-ore-bearing explosion pipes is accompanied by a partial removal of mercury.